MODELS AS A PRIVILEGED ELEMENT IN THE ARCHITECTURE EXHIBITIONS, TWO STUDY CASES. - Gomes, L.; Mendes, P. (Conferência Versatility of the building space, 2021)
Very often architecture exhibitions present representations of buildings and spaces. Drawings, pictures and models are exposed in order to show an absent entity: the building, the site and the users. Somehow we are facing a paradox. The representation elements aim to present the piece of architecture and its essence, but the real experience of architecture, as a multidimensional experience, is absent. The major theme of the investigation enquires about the use of models on architecture exhibitions. The investigation explores the range of use and appliance of models as a communication and simulation tool. Two exhibitions, in the Portuguese context, will be analysed and compared. Until renaissance drawings was not the central communication tool for architectural building concretion. Mostly, models were used to communicate the architectural design to the construction site. In a broad perspective models assumed the double role of simulation and communication of architecture for construction purposes. During the first half of 20th century, in Portugal, Architecture exhibition phenomenon has its beginning linked to teaching, through participation in exhibitions that brought together various artistic disciplines (Painting, Sculpture, Drawing, Architecture, etc.). With oscillations over time, the model guarantees a mandatory and essential presence in architectural exhibitions. It gains prominence, and even autonomy vis-à-vis the projects represented, in the last decades of the 20th century. The exhibition selection of study cases is developed in two specific cases. Both expose housing examples from 20th and 21st century. It is expected to identify the exhibition constants and variables issues. This way it is possible to clarify the architectonic use of models and establish patterns and typologies of model use.